ANALYSIS OF THE ROLE OF HOTEL TAX EFFECTIVENESS AND CONTRIBUTION TO CILACAP REGIONAL INCOME - Ardiansyah, Adit; Putra, Bally Brilian; Wicaksono, Galih; Inayah, Resvi (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2022)
To strengthen the economy of Cilacap Regency, fiscal policy is carried out based on Law No. 28 of 2009 concerning Regional Taxes and Regional Levies. The Cilacap Regency Government collects local taxes, one example is hotel tax collection. The local tax is one of the contributors to regional original income (PAD). This research was conducted to find out how effective and contribute hotel taxes are to Cilacap Regency's Local Revenue. The method used in this research is quantitative descriptive, by taking data from the last three years, namely 2019-2021. The data are secondary from the Cilacap Regency Central Bureau of Statistics (BPS). The results of the study show that the effectiveness of hotel taxes from year to year is very effective. Meanwhile, the contribution of hotel taxes to PAD is still lacking every year. So that it can be a reference for the Cilacap Regency government in improving its strategy for collecting taxes, especially hotel taxes,- so that Cilacap Regency Regional Original Revenue can continue to increase